2018
DOI: 10.1186/s12885-018-4796-5
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for predicting risk of locoregional recurrence and distant metastases for esophageal cancer patients after radical esophagectomy

Abstract: BackgroundThe aim of this study was to develop nomograms for predicting the risk of locoregional recurrence or distant metastasis in esophageal cancer patients who were treated with esophagectomy and regional lymphadenectomy.MethodsThe clinicopathologic data of 408 esophageal cancer patients after esophagectomy and regional lymphadenectomy were analyzed in this study. Univariate and multivariate COX regression analyses were used to test the association between the clinicopathologic data and the risk of locoreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Nomograms are frequently used not only for predicting survival in patients with all types of cancer but also for successfully quantifying risk prediction according to clinicopathological variables. [12][13][14][15] Although many of the available decision tools, such as CancerMath, 16 PREDICT 17 and the ipsilateral breast tumor recurrence program (IBTR), 18,19 have been established to predict survival probability in breast cancer patients, none of these tools are established specially based on the post-mastectomy breast cancer with pN0-1 without adjuvant radiotherapy. As a result, we perform the present study to establish and validate a nomogram based on a large sample size for predicting prognosis of post-mastectomy breast cancer with pN0-1, but without adjuvant radiotherapy, which could be used for adjuvant treatment counseling after mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms are frequently used not only for predicting survival in patients with all types of cancer but also for successfully quantifying risk prediction according to clinicopathological variables. [12][13][14][15] Although many of the available decision tools, such as CancerMath, 16 PREDICT 17 and the ipsilateral breast tumor recurrence program (IBTR), 18,19 have been established to predict survival probability in breast cancer patients, none of these tools are established specially based on the post-mastectomy breast cancer with pN0-1 without adjuvant radiotherapy. As a result, we perform the present study to establish and validate a nomogram based on a large sample size for predicting prognosis of post-mastectomy breast cancer with pN0-1, but without adjuvant radiotherapy, which could be used for adjuvant treatment counseling after mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a recently retrospective study published by Muhsen S. et al, the authors found that nearly 85% of patients with T1-2N1 could spare PMRT due to the low incidence of LRR [10], As a result, the role of adjuvant postmastectomy radiotherapy (PMRT) in early stage breast cancer remains controversial, and an accurate prognostic indicator to identify patients who at high risk for recurrence is clearly needed for physicians when giving individualized clinical decision making. Nomograms are frequently used not only for predicting survival in patients with all types of cancer but also for successfully quantifying risk prediction according to clinicopathological variables [11][12][13][14]. Although many of the available decision tools, such as CancerMath [15], PREDICT [16] and the ipsilateral breast tumor recurrence program (IBTR) [17,18], have been established to predict survival probability in breast cancer patients, none of these tools are established specially based on the post-mastectomy breast cancer with pN0-1 without adjuvant radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms have been widely proposed as new standards to predict the occurrence and prognosis of various cancer types, including esophageal cancer (13), rectal cancer (14), bladder cancer (15). With regard to prostate cancer, several groups have investigated prognostic nomograms in prostate cancer (1618).…”
Section: Introductionmentioning
confidence: 99%